Glass production and trade in the Early Islamic Persian Gulf - Fergadiotou, Elisavet (2020)
This thesis aims to provide the first statistically coherent interdisciplinary study of 7th to 10th century AD glass from the Persian Gulf. It is designed to contribute in a new way to the study of production and trade of glass along part of the ‘Spice Route’. It will focus on glass excavated in northern Kuwait and in Unguja Ukuu, Africa. The objectives of the thesis are to understand 1) what were the sources of glass in the 7th -9th century AD Persian Gulf, 2) were Bașra (southern Iraq) and Siraf (southern Iran) early Islamic primary production centers for glass, and 3) what types of early Islamic glass were traded in the Persian Gulf and in Unguja Ukuu, Africa within the context of ‘proto-globalization’? Glass production and trade in the earlyIslamic Persian Gulf (7th to 8th century AD) remains one of the least investigated fields of enquiry in recent scholarship and has become a topic of interest for those seeking to identify primary glass production zones and the geological origins of glass raw materials. There was a time when the glass manufacture was an established industry in the Persian Gulf (Pinder-Wilson,1963:33). The evidence is as near as conclusive as possible and prove that a thriving industry was already flourishing in Egypt, Syria, Iran and Iraq when these lands conquered by Muslims in the course of the 7th century AD (Lamm,1930:496-8;Lamm1935:8;Charleston,1942:217;Saldern,1966:17; Lukeins,1965:198;Hasson,1979:3;Klein,Lloyd,2000:58). Thus far, however, research in the Near East has focused primarily on the origins of Egypt and Syria rather than on Iran and Iraq (Freestoneet al.,2003;Henderson et al.,2004;Henderson et al.,2009). As a result, we lack valuable information about the thriving glassmaking industry on Persian soil, whose products met so wide distribution as wide as the Islamic influence at that time and as far as China and Japan. This thesis examines the glass production and the trade during the early Islamic period based on the findings of chemical analysis. Such a study has never been carried out for the Persian Gulf. A main goal of this research is to improve our knowledge of the early sources of glass manufacture in the Persian Gulf, to provide a basis for distinguishing the early Islamic Persian glass made in different parts of the world and to provide direct evidence for its trade.